The political–economic geography of foreign exchange trading - Wojcik, D; MacDonald-Korth, D; Zhao, S (Oxford University Press, 2016)
We propose a conceptual framework for the political-economic geography of foreign exchange trading, focusing on the causes and consequences of the relationship between the international currency system and international financial centres. The framework is used to analyse data for 1995-2013 demonstrating that while the trading activity has boomed, its structure by currency, with USD in the lead, has remained remarkably stable, and its concentration in the NYLON axis has grown. We show that Asian currencies and financial centres have made little progress in the foreign exchange market, and argue that any challenge of RMB to USD would require nothing short of an unprecedented geo-political and geo-economic transformation.